Hydrophobic co2 adsorbent with core-shell structure as well as preparation method and application thereof

The hydrophobic core-shell structured CO2 adsorbent addresses the challenge of maintaining high CO2 adsorption and hydrophobicity under humid conditions by using a microporous molecular sieve core with mesoporous silica and hydrophobic modifiers, enhancing adsorption performance in industrial exhaust gases.

JP2025066641AActive Publication Date: 2025-04-23INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024143120
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-08-23
Publication Date
2025-04-23
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

Existing CO2 adsorbents face challenges in maintaining high hydrophobicity and CO2 adsorption performance, especially under humid conditions, due to the competition between water and CO2 for adsorption sites and pore blockage issues from hydrophobic modifiers.

Method used

A hydrophobic core-shell structured CO2 adsorbent is developed, using a microporous molecular sieve as the core coated with mesoporous silica, with small molecular amines supported in the micropores and a hydrophobic modifier grafted onto the mesopores, enhancing hydrophobicity and CO2 adsorption without blocking pores.

Benefits of technology

The adsorbent achieves high CO2 adsorption capacity and improved hydrophobicity, maintaining performance under humid conditions, suitable for industrial applications in removing CO2 from aqueous and humid exhaust gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066641000001_ABST
    Figure 2025066641000001_ABST
Patent Text Reader

Abstract

To provide a hydrophobic CO2 adsorbent with a core-shell structure as well as a preparation method and application thereof.SOLUTION: A hydrophobic CO2 adsorbent with a core-shell structure uses a microporous molecular sieve as a core, with mesoporous silica coated outside the microporous molecular sieve as a shell. Micromolecular organic amine is loaded in micropores of the microporous molecular sieve, and a hydrophobic modifier is grafted in mesopores of the mesoporous silica.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of CO2 adsorption and capture, in particular to a hydrophobic core-shell structured CO2 adsorbent and its preparation method and use. [Background technology]

[0002] CO2 emissions are increasing day by day, causing serious harm to the atmospheric environment. CO2 has an insulating effect, which not only leads to the melting of glaciers, rising sea levels and the formation of acid rain, but also harms human health.

[0003] CO2 emissions from industrial exhaust gases are one of the main sources of CO2 in the atmosphere, and in order to achieve a low-carbon environment, the need to control CO2 emissions from exhaust gases is becoming increasingly urgent. CO2 capture technology is an effective way to achieve large-scale CO2 emission reductions, among which adsorption has the advantages of low energy consumption and high efficiency, and has great application potential in the field of CO2 capture from industrial exhaust gases. The adsorption materials commonly used in adsorption are zeolite, silica molecular sieve, carbon-based materials and MOFs materials as adsorbents. Zeolite and silica molecular sieve are low cost, easy to synthesize, and have high prospects for industrial application.

[0004] Molecular sieves have a large specific surface area and pore volume, which gives them a high CO2 adsorption capacity. CO2 is mainly physically adsorbed by the molecular sieve, which has a low heat of adsorption and is easy to regenerate. There are abundant siliceous hydroxyl groups on the surface of the molecular sieve pores, which have a strong affinity for water. Under hydrated conditions, H2O competes with CO2 for adsorption, resulting in a decrease in CO2 adsorption capacity. Industrial exhaust gases usually contain 15-20% H2O, and high concentrations of H2O reduce the molecular sieve's adsorption performance for CO2. To address this problem, Patent 202211318208.9 proposes a highly hydrophobic mesoporous Y-type molecular sieve and its preparation method, which adjusts the acidity of the molecular sieve by modifying the phosphorus of NaY molecular sieve, and treats it with high-temperature acidic steam in an oxygen-free environment to neutralize the free acid on the molecular sieve surface with weak alkali, and removes the free aluminum and sodium ions on the molecular sieve surface and in the pore cavities, thereby improving the hydrophobicity of the product. Although the hydrophobicity of the product has been improved, the pores of the modified molecular sieve have changed from micropores to mesopores of 2nm or more, and the alkali metal content has also been greatly reduced, so that it is clear that molecular sieves in this pore size range are unfavorable for CO2 adsorption.

[0005] Long-chain silyl groups usually have excellent hydrophobicity, and they are usually introduced into molecular sieves as hydrophobic modifiers to effectively increase the hydrophobicity of the molecular sieves. Although the CO2 adsorption performance of microporous molecular sieves is higher than that of mesoporous molecular sieves, their pore size is small, so if the hydrophobic modifier is directly introduced into the microporous molecular sieve, the pores will be blocked, affecting the CO2 transmitter and diffusion performance, and reducing the CO2 adsorption performance. Although the mesoporous molecular sieve has a large pore size, its CO2 adsorption performance is low. Introducing a hydrophobic modifier into the mesoporous molecular sieve can improve the hydrophobicity, but the CO2 adsorption capacity is limited, making it impossible to meet the CO2 adsorption amount required by the industry. Therefore, it is necessary to find a way to increase the hydrophobicity of the molecular sieve without reducing the molecular sieve's adsorption capacity for CO2, and to further improve the molecular sieve's CO2 adsorption performance, thereby providing a molecular sieve-type CO2 adsorbent that has good hydrophobicity and good CO2 adsorption performance. Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to provide a hydrophobic core-shell structure CO2 adsorbent and its preparation method and use in order to solve the above problems existing in the prior art. The hydrophobic core-shell structure CO2 adsorbent of the present invention uses a microporous molecular sieve as a core, and the outside of the microporous molecular sieve is coated with mesoporous silica as a shell. A small molecular organic amine is supported on the micropores of the molecular sieve. A hydrophobic modifier is grafted on the mesopores of the mesoporous silica. In the present invention, a small molecular amine is introduced into the micropores of the molecular sieve, and then a mesoporous silica layer is embedded on the surface to synthesize a core-shell structure micro-mesoporous composite material, and finally a hydrophobic modifier is introduced into the mesopores of the silica shell layer to obtain the final hydrophobic core-shell structure CO2 adsorbent. Meanwhile, when a small molecular amine is introduced into the micropores of the microporous molecular sieve, the small molecular amine does not block the pores, and the adsorption performance of CO2 can be effectively improved. On the other hand, mesopores are larger in size than micropores, and by grafting a hydrophobic modifier onto the mesopores of the silica shell layer, the pores of the adsorbent are less likely to be blocked, improving the hydrophobic performance of the adsorbent while also improving the chemical adsorption of CO2 with amine groups in the presence of a small amount of H2O (the presence of a small amount of H2O is favorable for the chemical reaction between CO2 and amine groups), promoting the adsorption action of the adsorbent, and improving the CO2 adsorption performance of the adsorbent under hydrous conditions. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention provides the following aspects.

[0008] A first aspect of the present invention is a hydrophobic core-shell structured CO2 adsorbent, which has a microporous molecular sieve as a core, and mesoporous silica coated on the outside of the microporous molecular sieve as a shell, in which a small molecule organic amine is supported in the micropores of the microporous molecular sieve, and a hydrophobic modifier is grafted to the mesopores of the mesoporous silica.

[0009] Furthermore, the microporous molecular sieve is ZSM-5, 13X, NaY, β, SAPO-34 or A-type microporous molecular sieve, the small molecule organic amine is propionamine, butylamine, ethylenediamine (EDA), diethylenetriamine (DETA), ethanolamine (MEA) or diethanolamine (DEA), and the hydrophobic modifier is octadecyltrimethoxysilane (ODTMS), octadecyltrichlorosilane (OTS) or normal octadecyltriethoxysilane (MSDS).

[0010] Grafting refers to the process in which one end (silane end) of a linear hydrophobic modifier enters the mesopores of silica and forms a covalent bond with the Si-OH in the silica. (The above hydrophobic modifier is essentially a silane coupling agent, which is an organosilicon compound containing a silane bond in its molecular structure. Its principle is to couple the organic part and the inorganic part through the chemical reaction of the silane bond, thereby enhancing the mechanical properties and chemical stability of the material. The silane group in the molecule of the silane coupling agent reacts chemically with the hydrogen atom in the Si-OH in the silica to form a Si-O-Si bond, and this bond is formed by a hydrolysis reaction method.)

[0011] A schematic diagram of the structure of the hydrophobic core-shell CO2 adsorbent is shown in Figure 1.

[0012] Preferably, the microporous molecular sieve is a 13X type microporous molecular sieve, the small molecule organic amine is butylamine, and the hydrophobic modifier is ODTMS.

[0013] A second aspect of the present invention is a method for preparing the hydrophobic core-shell structured CO2 adsorbent, comprising the steps of: The method includes the steps of immersing a microporous molecular sieve in a small molecular organic amine to obtain a molecular sieve having a small molecular amine supported in the micropores (denoted as ZN), embedding the molecular sieve having a small molecular amine supported in the micropores to form a mesoporous silica shell layer to obtain an amine-supported core-shell structured molecular sieve (denoted as ZN-Si), and hydrophobically modifying the surface of the amine-supported core-shell structured molecular sieve to obtain the hydrophobic core-shell structured CO2 adsorbent (denoted as ZN-Si-H).

[0014] Furthermore, immersing the microporous molecular sieve in a small molecular organic amine to obtain a molecular sieve having a small molecular amine supported in the micropores includes adding the microporous molecular sieve and the small molecular organic amine to a solvent, stirring and immersing, and spin-drying the solvent to obtain a molecular sieve having a small molecular amine supported in the micropores.

[0015] Furthermore, the mass ratio of the small molecular organic amine to the microporous molecular sieve is 0.001-0.2:1, the stirring and immersion is performed at room temperature, the stirring speed is 500 r / min, and the time is 4-6 hours.

[0016] Preferably, the mass ratio of the small molecule organic amine to the microporous molecular sieve is 0.002-0.1:1.

[0017] More preferably, the mass ratio of the small molecular organic amine to the microporous molecular sieve is 0.02 to 0.05.

[0018] Furthermore, embedding a molecular sieve carrying a small molecular amine in the micropores to form a mesoporous silica shell layer to obtain an amine-supported core-shell molecular sieve includes dissolving a template agent in water, sequentially adding a silicon source and the molecular sieve carrying a small molecular amine in the micropores, heating to perform a hydrothermal crystallization reaction, washing and drying after the reaction is completed, and performing Soxhlet extraction (removing the template agent to form a pore structure) to obtain an amine-supported core-shell molecular sieve.

[0019] In this process, the template acts as a mesoporous structure guide, and the silicon source self-organizes through a hydrothermal crystallization reaction to form mesoporous silica.

[0020] Further, the template agent is dissolved in water, the pH is adjusted to neutral with hydrochloric acid, a silicon source is added, the silicon source is added and stirred for 2 to 6 hours, a molecular sieve carrying a small molecular amine is added, the molecular sieve carrying a small molecular amine is added, and the mixture is stirred for another 6 to 24 hours and reheated to carry out a hydrothermal crystallization reaction.

[0021] Furthermore, after the Soxhlet extraction, the procedure also includes leaving the mixture to stand for 24 to 72 hours, washing, and drying.

[0022] Furthermore, the mass ratio of the molecular sieve having a small molecular amine supported in the micropores to the silicon source is 0.1-2.0:1, the mass ratio of the silicon source to the template agent is 0.2-4:1, the temperature of the hydrothermal crystallization reaction is 80-140°C, and the time is 6-24 hours, the silicon source is tetraethyl orthosilicate (TEOS), and the template agent is cetyltrimethylammonium bromide (CTAB).

[0023] Preferably, the mass ratio of the molecular sieve having a small molecular amine supported in its micropores to the silicon source is 0.2-1.2:1, the mass ratio of the silicon source to the template agent is 0.5-3:1, the temperature of the hydrothermal crystallization reaction is 80-120°C, and the time is 8-20 hours.

[0024] More preferably, the mass ratio of the molecular sieve having a small molecular amine supported in its micropores to the silicon source is 0.3-0.8:1, the mass ratio of the silicon source to the template agent is 1-2:1, the temperature of the hydrothermal crystallization reaction is 100-120°C, and the time is 12-18 hours.

[0025] Furthermore, the extractant for the Soxhlet extraction is a mixed solution of hydrochloric acid and an organic solvent, the organic solvent being ethanol or heptane, the mass ratio of the hydrochloric acid to the organic solvent being 0.5 to 3:1, and the concentration of the hydrochloric acid being 0.2 to 2.0M.

[0026] Preferably, the mass ratio of the hydrochloric acid to the organic solvent is 0.8-1.5:1, and the concentration of the hydrochloric acid is 0.8-1.8M.

[0027] More preferably, the mass ratio of the hydrochloric acid to the organic solvent is 1-1.2:1, and the concentration of the hydrochloric acid is 1.0-1.5M.

[0028] Furthermore, modifying the surface of the amine-supported core-shell molecular sieve to be hydrophobic to obtain the hydrophobic core-shell CO2 adsorbent includes dispersing the core-shell molecular sieve / silica composite material in a solvent, adding a hydrophobic modifier, reacting by heating, condensing and refluxing, and after the reaction is completed, washing, centrifuging and drying to obtain the hydrophobic core-shell CO2 adsorbent.

[0029] Furthermore, the mass ratio of the hydrophobic modifier to the core-shell molecular sieve / silica composite material is 0.001-0.5:1, the temperature of the heat condensation is 85° C., and the time is 6-24 hours.

[0030] Preferably, the mass ratio of the hydrophobic modifier to the core-shell molecular sieve / silica composite material is 0.01-0.3:1.

[0031] More preferably, the mass ratio of the hydrophobic modifier to the core-shell molecular sieve / silica composite material is 0.05-0.1:1.

[0032] A third aspect of the present invention is the use of the hydrophobic core-shell structured CO2 adsorbent in removing CO2 from aqueous industrial exhaust gases. Effect of the Invention

[0033] The present invention discloses the following technical effects.

[0034] (1) The hydrophobic core-shell structure CO2 adsorbent of the present invention has a microporous molecular sieve as a core, and the outside of the microporous molecular sieve is coated with mesoporous silica as a shell, and a small molecular organic amine is supported on the micropores of the microporous molecular sieve, and a hydrophobic modifier is grafted on the mesopores of the mesoporous silica. On the other hand, the present invention uses an adsorbent having a molecular sieve with a small molecular organic amine supported in the micropores as a core to adsorb CO2 into the micropores in the molecular sieve, and at the same time, the supported small molecular organic amine can increase the adsorption capacity of CO2, and the small molecular amine is less likely to block the micropores, so that the adsorption capacity of CO2 can be maximized. On the other hand, the surface of the pores of the conventional molecular sieve contains many hydroxyl groups, which makes it very hydrophilic, and therefore the adsorption ability of CO2 is hindered under water-containing conditions. The surface of the molecular sieve is coated with a layer of mesoporous silica as a shell layer, and a hydrophobic modifier is introduced into the mesoporous pores of the silica shell layer to improve the hydrophobicity of the molecular sieve and reduce the impact of moisture on the CO2 adsorption capacity. In addition, the size of the mesopores in the silica structure is large, so that hydrophobic groups can be introduced without blocking the pores of the molecular sieve, and the diffusion of CO2 in the adsorbent is not affected, and the hydrophobicity can be improved while improving the CO2 adsorption performance of the adsorbent. In addition, after the hydrophobicity of the adsorbent is improved, it does not mean that it does not absorb moisture at all, but only the adsorption performance to water is reduced, and the amount of adsorbed water is greatly reduced, and under water-containing conditions, low concentration H2O promotes the chemical adsorption of CO2 by small molecular organic amines in the molecular sieve, promotes the production of urethane, which is a chemical adsorption product, and improves the CO2 adsorption performance of the adsorbent under water-containing conditions. From the above, the hydrophobic core-shell structure CO2 adsorbent of the present invention can simultaneously satisfy the dual improvement of hydrophobicity and CO2 adsorption performance.

[0035] (2) The hydrophobic core-shell structured CO2 adsorbent of the present invention has a high CO2 adsorption capacity at 25°C, with an adsorption capacity as high as 177 mg / g, and has good hydrophobicity. Under the condition of an H2O concentration of 6%, the CO2 adsorption capacity of this adsorbent is not decreased but increased compared to microporous molecular sieves, and the CO2 permeation time is extended. It is suitable for recovering CO2 in aqueous industrial exhaust gases and humid industrial exhaust gases, and is particularly suitable for removing CO2 from aqueous and humid exhaust gases in industries such as cement and steel, and is expected to be applied industrially.

[0036] (3) The present invention does not involve any complicated steps in the process of preparing the hydrophobic core-shell structured CO2 adsorbent, and the preparation process is simple, highly versatile, and widely applicable, which contributes to industrial production and popularization. [Brief description of the drawings]

[0037] In the following, in order to more clearly explain the embodiments of the present invention or aspects in the prior art, the drawings necessary for the embodiments will be briefly described. However, the drawings in the following description are only some embodiments of the present invention, and it is obvious that those skilled in the art can obtain other drawings based on these drawings without exerting creative efforts. [Figure 1] FIG. 2 is a structural schematic diagram of the hydrophobic core-shell structure CO2 adsorbent of the present invention. [Diagram 2] 1 shows the CO2 permeation curves of the 13X-N-Si-H adsorbent and the 13X-type microporous molecular sieve prepared in Example 2 under hydrated conditions, and the CO2 permeation curve of the 13X-type microporous molecular sieve under anhydrous conditions. [Diagram 3] 1 shows the H2O adsorption isotherms at 25°C for the 13X-N-Si-H adsorbent and the 13X-type microporous molecular sieve prepared in Example 2; [Figure 4] FIG. 2 shows the CO2 adsorption capacity at 25° C. of the 13X-N-Si-H adsorbent and the 13X-type microporous molecular sieve prepared in Example 2. [Diagram 5]1 shows the thermogravimetric loss curves of the 13X-N-Si-H adsorbent and the 13X-type microporous molecular sieve. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] Although some exemplary embodiments of the present invention will now be described in detail, this detailed description should not be construed as limiting the present invention, but should be understood as a more detailed description of some aspects, features and embodiments of the present invention.

[0039] It is to be understood that the terms described in the present invention are intended to describe particular embodiments and are not intended to limit the present invention. It is also to be understood that the numerical ranges in the present invention are specifically disclosed at every intermediate value between the upper and lower limits of the range. Any stated value or intermediate value within a stated range, as well as any other stated value or intermediate value within that range, are also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded within the range.

[0040] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art of the present invention. Although the present invention describes only preferred methods and materials, methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention. All publications mentioned herein are incorporated by reference to disclose and describe the methods and / or materials related thereto. In the event of any conflict with any incorporated publication, the contents of this document shall control.

[0041] It will be apparent to those skilled in the art that many modifications and variations can be made to the specific embodiments of the present specification without departing from the scope or spirit of the present invention. Other embodiments of the present specification will be apparent to those skilled in the art. The present specification and examples are given by way of example only.

[0042] As used herein, "comprising," "including," "having," "containing," and the like are all open-ended terms, meaning including but not limited to. EXAMPLES

[0043] Example 1 (1) Preparation of molecular sieves with small amines supported on micropores 5.00g of 13X type microporous molecular sieve powder is placed in a round-bottom flask, ethanol is added as a solvent, 0.75g of ethylenediamine is added, and the mixture is stirred and immersed at room temperature for 4 hours at a stirring speed of 500r / min. During stirring, the ethylenediamine dissolves and is immersed and supported in the micropores of the molecular sieve. After the ethylenediamine is immersed and supported, the flask is transferred to a rotary evaporator and evaporated at 60°C until the solvent is completely evaporated, and a molecular sieve with small molecular amine supported in the micropores is obtained, which is denoted as ZN.

[0044] (2) Preparation of amine-loaded core-shell molecular sieves Dissolve 1.50g of template agent CTAB in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to neutral, and stir until dissolved. Then add 4.55g of TEOS as a silicon source and continue stirring for 2 hours. Then add 4.62g of ZN powder and continue stirring for 6 hours. Then, transfer the mixture to a high-pressure reactor and carry out hydrothermal crystallization reaction at a hydrothermal temperature of 80°C for 10 hours. After hydrothermal crystallization reaction, wash the sample with a large amount of deionized water and dry it to obtain a solid powder. The above solid powder is dissolved in a mixture of hydrochloric acid and ethanol 0.8M (mass ratio of hydrochloric acid and ethanol is 0.5:1), and perform Soxhlet extraction to remove the template agent and form a pore structure. After standing for 24 hours, wash with deionized water 5 times and dry to obtain an amine-supported core-shell structure molecular sieve, which is designated as ZN-Si.

[0045] (3) Preparation of hydrophobic core-shell structured CO2 adsorbent Take another flask, add anhydrous ethanol to the flask as a solvent, add 4.20g of ZN-Si and 1mL of deionized water, and after stirring at room temperature to disperse uniformly, add 0.12g of hydrophobic modifier ODTMS, and condense and reflux at 85℃ to make the alkyl end of the linear hydrophobic modifier enter the mesopores of the silica and form a covalent bond with the Si-OH in the silica to be grafted onto the silica. The condensation and reflux time is 6 hours, and after the reaction is completed, the solid-liquid mixture is washed with ethanol and deionized water 5 times each, centrifuged and dried to obtain a hydrophobic core-shell structure CO2 adsorbent, which is denoted as ZN-Si-H.

[0046] Example 2 (1) Preparation of molecular sieves with small amines supported on micropores 5.00g of 13X type microporous molecular sieve powder is placed in a round-bottom flask, ethanol is added as a solvent, 0.25g of butylamine is added, and the mixture is stirred and immersed at room temperature for 6 hours at a stirring speed of 500r / min. During stirring, the butylamine dissolves and is immersed and supported in the micropores of the molecular sieve. After the butylamine is immersed and supported, the flask is transferred to a rotary evaporator and evaporated at 60°C until the solvent is completely evaporated, and a molecular sieve with small molecular amine supported in the micropores is obtained, which is denoted as ZN.

[0047] (2) Preparation of amine-loaded core-shell molecular sieves Dissolve 3.00g of template agent CTAB in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to neutral, stir until dissolved, add 3.06g of TEOS as a silicon source, continue stirring for 6 hours, then add 1.84g of ZN powder, continue stirring for 24 hours, transfer the mixture to a high-pressure reactor, carry out hydrothermal crystallization reaction at a hydrothermal temperature of 100 ° C for 18 hours, wash the sample after hydrothermal crystallization reaction with a large amount of deionized water and dry to obtain a solid powder. The above solid powder is dissolved in a 1.5M mixture of hydrochloric acid and ethanol (mass ratio of hydrochloric acid to ethanol is 0.5:1), perform Soxhlet extraction to remove the template agent and form a pore structure, leave it for 48 hours, wash with deionized water five times and dry to obtain an amine-supported core-shell structure molecular sieve, which is designated as ZN-Si.

[0048] (3) Preparation of hydrophobic core-shell structured CO2 adsorbent Take another flask, add anhydrous ethanol to the flask as a solvent, add 2.51g of ZN-Si and 1mL of deionized water, and after stirring at room temperature to disperse uniformly, add 0.25g of hydrophobic modifier ODTMS, and condense and reflux at 85℃ to make the alkyl end of the linear hydrophobic modifier enter the mesopores of the silica and form a covalent bond with the Si-OH in the silica to be grafted onto the silica. The condensation and reflux time is 20 hours, and after the reaction is completed, the solid-liquid mixture is washed with ethanol and deionized water five times each, centrifuged and dried to obtain a hydrophobic core-shell structure CO2 adsorbent, which is designated as ZN-Si-H.

[0049] Example 3 (1) Preparation of molecular sieves with small amines supported on micropores 8.0g of 13X type microporous molecular sieve powder is placed in a round-bottom flask, ethanol is added as a solvent, 1.6g of butylamine is added, and the mixture is stirred and immersed at room temperature for 6 hours at a stirring speed of 500r / min. During stirring, the butylamine dissolves and is immersed and supported in the micropores of the molecular sieve. After the butylamine is immersed and supported, the flask is transferred to a rotary evaporator and rotatively evaporated at 60°C until the solvent is completely evaporated, and a molecular sieve with small molecular amine supported in the micropores is obtained, which is denoted as ZN.

[0050] (2) Preparation of amine-loaded core-shell molecular sieves Dissolve 1.12g of template agent CTAB in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to neutral, stir until dissolved, add 4.43g of TEOS as silicon source, continue to stir for 5 hours, then add 8.79g of ZN powder and continue to stir for 12 hours, then transfer the mixture to a high-pressure reactor and carry out hydrothermal crystallization reaction at a hydrothermal temperature of 140 ° C for 24 hours, wash the sample after hydrothermal crystallization reaction with a large amount of deionized water and dry to obtain a solid powder. Dissolve the above solid powder in a mixture of hydrochloric acid and ethanol 0.6M (mass ratio of hydrochloric acid and ethanol is 0.5:1), perform Soxhlet extraction to remove the template agent and form a pore structure, leave it for 72 hours, wash with deionized water 5 times and dry to obtain an amine-supported core-shell structure molecular sieve, which is designated as ZN-Si.

[0051] (3) Preparation of hydrophobic core-shell structured CO2 adsorbent Take another flask, add anhydrous ethanol to the flask as a solvent, add 3.64g of ZN-Si and 1mL of deionized water, and after stirring at room temperature to disperse uniformly, add 1.75g ​​of hydrophobic modifier ODTMS, and condense and reflux at 85℃ to insert the alkyl end of the linear hydrophobic modifier into the mesopores of the silica, form a covalent bond with the Si-OH in the silica, and graft onto the silica. The condensation and reflux time is 22 hours, and after the reaction is completed, the solid-liquid mixture is washed with ethanol and deionized water five times each, centrifuged and dried to obtain a hydrophobic core-shell structure CO2 adsorbent, which is designated as ZN-Si-H.

[0052] Example 4 Same as Example 2, except for replacing ethylenediamine with butylamine in step (1).

[0053] Example 5 Same as Example 2, except that in step (1) the 13X type microporous molecular sieve is replaced by a ZSM-5 type microporous molecular sieve.

[0054] Example 6 This is the same as in Example 2, except that ODTMS is replaced with OTS in step (3).

[0055] Comparative Example 1 Same as Example 1, except that in step (1) ethylenediamine is replaced with polyethyleneimine.

[0056] Comparative Example 2 (1) Preparation of core-shell molecular sieves Dissolve 1.50g of template agent CTAB in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to neutral, and stir until dissolved. Then add 4.55g of TEOS as a silicon source and continue stirring for 2 hours. Then add 4.62g of 13X type microporous molecular sieve powder and continue stirring for 6 hours. Then, transfer the mixture to a high-pressure reactor and carry out hydrothermal crystallization reaction at a hydrothermal temperature of 80°C for 10 hours. After hydrothermal crystallization reaction, wash the sample with a large amount of deionized water and dry it to obtain a solid powder. The above solid powder is dissolved in a mixture of hydrochloric acid and ethanol 0.8M (mass ratio of hydrochloric acid and ethanol is 0.5:1), and perform Soxhlet extraction to remove the template agent and form a pore structure. After standing for 24 hours, wash with deionized water five times and dry to obtain a core-shell structure molecular sieve, which is designated as Z-Si.

[0057] (2) Preparation of hydrophobic core-shell structured CO2 adsorbent Take another flask, add anhydrous ethanol to the flask as a solvent, add 4.20g of Z-Si and 1mL of deionized water, and after stirring at room temperature to disperse uniformly, add 0.12g of hydrophobic modifier ODTMS, and condense and reflux at 85℃ to make the alkyl end of the linear hydrophobic modifier enter the mesopores of the silica and form a covalent bond with the Si-OH in the silica to be grafted onto the silica. The condensation and reflux time is 6 hours, and after the reaction is completed, the solid-liquid mixture is washed with ethanol and deionized water five times each, centrifuged and dried to obtain a hydrophobic core-shell structure CO2 adsorbent, which is denoted as Z-Si-H.

[0058] Effect verification 1. CO2 permeability of adsorbent The hydrophobic core-shell structure CO2 adsorbent prepared in Example 2 was subjected to a CO2 permeation performance test under a water-containing condition. Test method and conditions: Fixed bed-mass spectrometry is used to evaluate the effect of H2O on the permeation performance of CO2. The CO2 concentration is 15%, H2O concentration is 6%, equilibrium gas is N2, total gas amount is 100mL / min, adsorbent usage amount is 1000mg, adsorption temperature is 25℃, adsorption time is 8 minutes, and the adsorbent is pretreated in a drying box at 100℃ before the test to prepare it in advance. Before the start of the experiment, the adsorbent is pretreated at 100℃, 100mL / min, and under N2 atmosphere for 1 hour. The CO2 permeation performance of the 13X type microporous molecular sieve under a water-containing condition (same test method as above) and anhydrous condition (same procedure as above except that the gas does not contain water) is used as a control.

[0059] The test results are as follows:

[0060] Figure 2 shows the CO2 permeation curves of the 13X-N-Si-H adsorbent and the 13X-type microporous molecular sieve prepared in Example 2 under hydrous conditions, and the CO2 permeation curve of the 13X-type microporous molecular sieve under anhydrous conditions. As can be seen from Figure 2, at 25 ℃, under anhydrous conditions, the CO2 on the 13X-type microporous molecular sieve begins to permeate in about 1 minute, and after adding H2O, the permeation time of CO2 on the 13X-type microporous molecular sieve is shortened to 1 / 3, but the CO2 permeation time of the 13X-N-Si-H adsorbent under hydrous conditions is extended, which shows that the CO2 adsorption performance of the 13X-N-Si-H adsorbent under hydrous conditions is not inhibited by H2O, and compared with the CO2 adsorption performance of the 13X-type microporous molecular sieve under anhydrous conditions, the CO2 adsorption performance of the 13X-N-Si-H adsorbent under hydrous conditions is improved.

[0061] 2. Adsorption performance of the adsorbent against H2O (hydrophobicity of the adsorbent) The HO adsorption isotherm of the adsorbent was measured by a physical adsorption apparatus, and the adsorption temperature was 25°C. The HO adsorption isotherm of the 13X-N-Si-H adsorbent prepared in Example 2 and the 13X-type microporous molecular sieve at 25°C is shown in Figure 3. As can be seen from Figure 3, when the relative pressure is 1, the adsorption capacity of the 13X-type microporous molecular sieve for HO is 450 cm 3 / g, whereas the adsorption capacity of the 13X-N-Si-H adsorbent for HO is 150 cm 3 / g, and the adsorption performance for HO was reduced by 2 / 3, indicating that the hydrophobicity of the adsorbent was improved after hydrophobic modification. The test results of the amount of HO adsorption at 25°C for the adsorbents prepared in the remaining Examples and Comparative Examples are shown in Table 1.

[0062] 3. CO2 adsorption capacity The CO2 adsorption capacity is evaluated by a thermogravimetric analyzer, the concentration of CO2 is 15%, the equilibrium gas is N2, the adsorption temperature is 25 °C, the adsorption time is 120 min, and the amount of adsorbent used is 10-20 mg. Before the test, the adsorbent is pretreated in a drying box at 100 °C for 20 h to prepare it in advance.

[0063] FIG. 4 is a graph showing the CO2 adsorption capacity of the 13X-N-Si-H adsorbent and the 13X-type microporous molecular sieve prepared in Example 2 at 25°C. As can be seen from FIG. 4, the saturated adsorption capacity of the 13X-type microporous molecular sieve for CO2 under anhydrous conditions is 110mg / g, and the CO2 saturated adsorption capacity of the 13X-N-Si-H adsorbent after modification reaches 177mg / g, and the CO2 adsorption capacity is improved by 60.9%, which shows that the CO2 adsorption capacity of the adsorbent is greatly improved by the immersion modification of small molecular amine. The test results of the CO2 adsorption amount at 25°C of the adsorbents prepared in the remaining examples and comparative examples are shown in Table 1.

[0064] In addition, the CO2 adsorption amount of the adsorbents prepared in each Example and Comparative Example in 6%-H2O was tested under conditions of CO2 concentration 15%, H2O concentration 6%, equilibrium gas N2, and adsorption temperature 25°C, and the test results are shown in Table 1.

[0065] [Table 1]

[0066] 4. Thermal stability test The 13X-N-Si-H adsorbent prepared in Example 2 is subjected to thermogravimetric analysis, and the 13X-type microporous molecular sieve is used as the control. The experimental parameters are set as shown in Table 2 (the adsorbent is placed in the thermogravimetric analyzer, then stabilized at 25°C for 60 minutes, and then heated to perform the thermogravimetric experiment).

[0067] [Table 2]

[0068] The thermal weight loss curves of the 13X-N-Si-H adsorbent and the 13X-type microporous molecular sieve prepared in Example 2 are shown in Figure 5. As can be seen from Figure 5, the 13X-type microporous molecular sieve has high thermal stability, and the framework structure is stable even at 1000 ° C. The weight loss of the 13X-type microporous molecular sieve before 200 ° C. is caused by the desorption of H2O and impurity gases (the adsorbent absorbs gases such as H2O and CO2 in the air in the natural environment). The weight loss of the modified 13X-N-Si-H adsorbent before 200 ° C. is also caused by the desorption of H2O and impurity gases (the adsorbent absorbs gases such as H2O and CO2 in the air in the natural environment). The weight loss between 200 and 500 °C is due to the volatilization of the soaked small molecule amine, and the weight loss between 500 and 800 °C is due to the decomposition of the hydrophobic modifier, and the 13X-N-Si-H adsorbent can keep good thermal stability at 200 °C.

[0069] The above-described embodiments merely describe preferred aspects of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the aspects of the present invention without departing from the design spirit of the present invention should be included in the scope of protection defined by the claims of the present invention.

Claims

1. Hydrophobic core-shell structure CO 2 Adsorbent for CO in water-containing industrial exhaust gas 2 wherein the removal temperature is 25° C. The hydrophobic core-shell structure CO 2 The adsorbent has a microporous molecular sieve as a core, the microporous molecular sieve is coated with mesoporous silica as a shell, a small molecule organic amine is supported in the micropores of the microporous molecular sieve, and a hydrophobic modifier is grafted to the mesopores of the mesoporous silica; the microporous molecular sieve is ZSM-5, 13X, NaY, β, SAPO-34 or A-type microporous molecular sieve; the small molecule organic amine is one or more of propionamine, butylamine, ethylenediamine, diethylenetriamine, ethanolamine, diethanolamine; the hydrophobic modifier is octadecyltrimethoxysilane, octadecyltrichlorosilane or normal octadecyltriethoxysilane; The hydrophobic core-shell structure CO 2 The method for preparing the adsorbent is as follows: A microporous molecular sieve is immersed in a small molecular organic amine to obtain a molecular sieve having a small molecular amine supported in the micropores, the molecular sieve having a small molecular amine supported in the micropores is embedded in the micropores to form a mesoporous silica shell layer, an amine-supported core-shell structured molecular sieve is obtained, the surface of the amine-supported core-shell structured molecular sieve is hydrophobically modified, and the hydrophobic core-shell structured CO 2 obtaining an adsorbent; The hydrophobic core-shell structure CO2 is characterized in that the step of embedding a molecular sieve carrying a small molecular amine in the micropores to form a mesoporous silica shell layer and obtaining an amine-supported core-shell structure molecular sieve includes dissolving a template agent in water, sequentially adding a silicon source and the molecular sieve carrying a small molecular amine in the micropores, heating the mixture to perform a hydrothermal crystallization reaction, and washing, drying, and Soxhlet extraction to obtain an amine-supported core-shell structure molecular sieve. 2 Adsorbent for CO in water-containing industrial exhaust gas 2 Use in the removal of.

2. The use according to claim 1, characterized in that the step of immersing the microporous molecular sieve with a small molecular organic amine to obtain a molecular sieve having a small molecular amine supported in the micropores includes adding the microporous molecular sieve and the small molecular organic amine to a solvent, stirring and immersing, and spin-drying the solvent to obtain a molecular sieve having a small molecular amine supported in the micropores.

3. The use according to claim 2, characterized in that the mass ratio of the small molecule organic amine to the microporous molecular sieve is 0.001-0.2:1, the stirring and soaking is carried out at room temperature, the stirring speed is 500 r / min, and the time is 4-6 hours.

4. The use according to claim 1, characterized in that the mass ratio of the molecular sieve with a small molecular amine supported in the micropores to the silicon source is 0.1-2.0:1, the mass ratio of the silicon source to the template agent is 0.2-4:1, the temperature of the hydrothermal crystallization reaction is 80-140°C, and the time is 6-24 hours, the silicon source is tetraethyl orthosilicate, and the template agent is cetyltrimethylammonium bromide.

5. The surface of the amine-supported core-shell structured molecular sieve is hydrophobically modified, and the hydrophobic core-shell structured CO 2 The adsorbent is obtained by dispersing the amine-supported core-shell molecular sieve in a solvent, adding a hydrophobic modifier, and reacting by heating, condensing and refluxing. After the reaction is completed, the mixture is washed, centrifuged and dried to obtain the hydrophobic core-shell molecular sieve. 2 2. Use according to claim 1, characterised in that it comprises obtaining an adsorbent.

6. The use according to claim 5, characterized in that the mass ratio of the hydrophobic modifier to the amine-loaded core-shell molecular sieve is 0.001-0.5:1, the temperature of the heating and condensing is 85°C, and the time is 6-24 hours.